Fluid-dynamic model of hydrocarbon accumulation in salt-strike-slip structures of the Dnieper-Donetsk depression - Василенко, О. Л. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The article examines the problems of Geology and petroleum potential of a new type in the tectonic structures of salt-strike-slip structures (SSSS), established by the author in the Dnieper-Donetsk depression (DDD).Depending on geodynamic conditions strike-slip within the salt dome shaft are formed of a convergence (compression) and divergence (stretching) zone. Inside these zones areas of transtension and transgression are allocated. These sections meet five morphogenetic types of salt-strike-slip structures: Chutivsky, Vesnyansky, East-Medvedovsky, Melikhovskay and Kochubeevsky.Developed a fluid dynamic spatial model of hydrocarbon accumulations formation in SSSS allows to predict migration paths of hydrocarbons and allocate traps in natural reservoirs. In the formations of deposits in SSSS a decisive influence have the processes of horizontal compression and horizontal strike-slip. These processes are the basis for fluid-dynamic models of hydrocarbon deposits based on the structural features of SSSS. It covers: 1) the formation of decomposition zones as the source and useful volume for accumulation of hydrocarbons; 2) following upward vertical migration of fluid flows of loosened zones on plots of shear tectonic dislocations; 3) the formation of hydrocarbon traps under reliable salt confining beds. The important factor in the localization of hydrocarbons in the SSSS is a complex tectonic dislocation where a significant role is played by areas of ancient deep faults, which are channels for the fluid heat and mass transfer.It is established that traditional gas condensate field is characterized by: a secondary reservoirs of fractured-porous type; component two-phase (gas-condensate); united gas-water contact controlling massive sheet deposit; maximum overpressure in the roof deposits under salt lid and anticlinal, mass of reservoir traps. In fields dedicated to SSSS, characteristics of oil and gas are: a wide range of reservoir types with depth; a wide range of phase state of hydrocarbons; absence of a common gas-water contact; multilayered type deposits; the absence of abnormally high reservoir pressure peaks; reservoir types in combined non-anticlinal traps.